2020
DOI: 10.3389/fendo.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Reverse Transcriptase (TERT) Regulation in Thyroid Cancer: A Review

Abstract: Telomerase reverse transcriptase (TERT) is the catalytic subunit of the enzyme telomerase and is essential for telomerase activity. Upregulation of TERT expression and resulting telomerase activity occurs in the large majority of malignancies, including thyroid cancer. This upregulation results in continued cellular proliferation and avoidance of cellular senescence and cell death. In this review we will briefly introduce TERT and telomerase activity as it pertains to thyroid cancer and, highlight the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 75 publications
(97 reference statements)
1
22
0
2
Order By: Relevance
“…TERT alterations may lead to activation of telomerase 15 . The prevalence of both TERT mutations and TERT amplification increases in advanced stages of disease, 15 and both TERT mutations, and TERT amplification are associated with increased TERT expression 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TERT alterations may lead to activation of telomerase 15 . The prevalence of both TERT mutations and TERT amplification increases in advanced stages of disease, 15 and both TERT mutations, and TERT amplification are associated with increased TERT expression 16 .…”
Section: Discussionmentioning
confidence: 99%
“…TERT alterations may lead to activation of telomerase 15 . The prevalence of both TERT mutations and TERT amplification increases in advanced stages of disease, 15 and both TERT mutations, and TERT amplification are associated with increased TERT expression 16 . We also found that PTCs with a TERT promoter mutation were more likely to have a TERT amplification (13%) than wildtype TERT tumors (3.2%, Figure 3), and tumors harboring both TERT alterations had the highest levels TERT expression, suggesting that the two TERT alterations may work in concert.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some problems. Approximately 30% of DTC patients are downstaged to stage I or II, so there are too few patients with stage III and IV disease [6,9], and there is no molecular profile of clinical prognostic significance that has recently emerged [10,11]. In addition, a large multicenter cohort study showed the poor predictability of TNM-8 in the CSS of follicular thyroid cancer (FTC) patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…TERT expression can be upregulated through several mechanisms including promoter mutations, TERT gene copy number alterations, increased promoter methylation and histone modifications [ 14 18 ]. These TERT-related genetic aberrations have been implicated in thyroid cancer with particular prevalence in aggressive subtypes [ 15 , 16 ]. They have a high specificity and positive predictive value for thyroid cancer [ 19 ] and have been associated with poorer patient outcomes, including a greater risk of death [ 14 , 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%